GPU solutions to multi-scale problems in science and engineering - Wang, Long; Chi, Xuebin; Johnsson, Lennart; Ge, Wei; Shi, Yaolin; Yuen, David A. (Lecture Notes in Earth System Sciences, 2013)
This book covers the new topic of GPU computing with many applications involved, taken from diverse fields such as networking, seismology, fluid mechanics, nano-materials, data-mining , earthquakes ,mantle convection, visualization. It will show the public why GPU computing is important and easy to use. It will offer a reason why GPU computing is useful and how to implement codes in an everyday situation.